21st century skills: A commitment to the training of graduates in inclusive education settings - Lombana Ruiz, Sonia; Bolívar Castañeda, Cindy (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2020)
This article presents a pedagogical experience focused on analyzing the tools that graduates in training must develop to build effective processes of inclusive education. Starting from the concept of "understanding", used as the central point of the process, three articulating axes are defined: 1) Legal; Conceptualization; and 3) Methodological from the XXI century skills. Finally, a series of findings that arise from an analytical and critical exercise are presented.